ANALISIS KELAYAKAN FINANSIAL SASUKE (SARI SUSU KEDELAI) DI FAKULTAS VOKASI UNTAG SURABAYA - Wahyu Kanti Dwi Cahyani; Dian Novitasari (AGROINTEK, 2021)
Sasuke (Soy milk extract) is one of the products of a business unit that is run at the Faculty of Vocational Agroindustry, Untag Surabaya. Soy milk extract has many nutritional content including fiber and high protein. These efforts have not yet been carried out by a financial feasibility analysis. The purpose of this study was to determine the financial feasibility of Sasuke's business. This research uses primary data and is quantitative in nature. Then, a financial analysis consisting of the NPV, PBP, and B/C ratio analysis. This research was conducted at the Agroindustry Laboratory of the Vocational Faculty of Untag Surabaya. The results showed that Sasuke's business was feasible. Evidenced by the results of analysis for 10 years resulting in the value of NPV = IDR 103,762,210 (NPV 0), B / C ratio = 1,105 (B / C ratio 1), and capital will return to PBP = 1,049 years = 367 days.